Investment, integration, and innovation: Fostering diversity, equity, and inclusion across the HEALthy Brain and Child Development (HBCD) Study consortium - Murray, Traci M.; Slopen, Natalie (Developmental cognitive neuroscience, 2024)
The HEALthy Brain and Child Development (HBCD) Study, a multi-site prospective longitudinal cohort study, will examine human brain, cognitive, behavioral, social, and emotional development beginning prenatally and planned through early childhood. From the outset, the HBCD Study integrated diversity, equity, and inclusion (DEI) into its core mission, with key elements like an Associate Director for DEI, a DEI values statement, and establishing a DEI committee to help ensure sustainable progress for the future. The DEI Coordinating Committee supports DEI efforts impacting members of the HBCD consortium, study participants, and the analysis and dissemination of HBCD data. Committee members include representatives from every study site and workgroup which contributes to DEI integration throughout the study. Committee activities include reviewing all measures and protocols, creating accountability metrics, and supporting training opportunities for consortium members. Several successes and lessons have been learned through the Committee’s activities like implementing consortium-wide unconscious bias training and changing the DEI leadership and committee structure. This article presents an overview of HBCD’s DEI components within HBCD and provides examples of collaborative efforts between the DEI Coordinating Committee and other workgroups. The article concludes with plans for future activities and recommendations for other large consortia considering formal DEI structures.